The Role of the 3-Hydroxy 3-Methylglutaryl Coenzyme A Reductase Cytosolic Domain in Karmellae Biogenesis - Profant, Deborah A. (The American Society for Cell Biology, 1999)
In all cells examined, specific endoplasmic reticulum (ER) membrane arrays are induced in response to increased levels of the ER membrane protein 3-hydroxy 3-methylglutaryl coenzyme A (HMG-CoA) reductase. In yeast, expression of Hmg1p, one of two yeast HMG-CoA reductase isozymes, induces assembly of nuclear-associated ER stacks called karmellae. Understanding the features of HMG-CoA reductase that signal karmellae biogenesis would provide useful insights into the regulation of membrane biogenesis. The HMG-CoA reductase protein consists of two domains, a multitopic membrane domain and a cytosolic catalytic domain. Previous studies had indicated that the HMG-CoA reductase membrane domain was exclusively responsible for generation of ER membrane proliferations. Surprisingly, we discovered that this conclusion was incorrect: sequences at the carboxyl terminus of HMG-CoA reductase can profoundly affect karmellae biogenesis. Specifically, truncations of Hmg1p that removed or shortened the carboxyl terminus were unable to induce karmellae assembly. This result indicated that the membrane domain of Hmg1p was not sufficient to signal for karmellae assembly. Using β-galactosidase fusions, we demonstrated that the carboxyl terminus was unlikely to simply serve as an oligomerization domain. Our working hypothesis is that a truncated or misfolded cytosolic domain prevents proper signaling for karmellae by interfering with the required tertiary structure of the membrane domain.